Bortezomib-cyclophosphamide-dexamethasone induction/consolidation and bortezomib maintenance for transplant-eligible newly diagnosed multiple myeloma: phase 2 multicenter trial. Issue 1 (31st December 2022) - Muranushi, Hiroyuki; Kanda, Junya; Kobayashi, Masayuki; Maeda, Takeshi; Kitano, Toshiyuki; Tsuji, Masaaki; Ueda, Yasunori; Ishikawa, Takayuki; Nohgawa, Masaharu; Watanabe, Mitsumasa; Imada, Kazunori; Moriguchi, Toshinori; et al.
ABSTRACT: Objectives: We conducted a phase II trial to prospectively evaluate the efficacy and safety of bortezomib-cyclophosphamide-dexamethasone (VCD) induction, autologous stem cell transplantation (ASCT), VCD consolidation, and bortezomib maintenance in transplant-eligible newly diagnosed multiple myeloma (NDMM) patients in Japan (UMIN000010542). Methods: From 2013 to 2016, 42 patients with a median age of 58 (range 42–65) years with NDMM were enrolled in 15 centers. The primary endpoint was the complete response (CR) /stringent CR (sCR) rate after transplantation, and overall/progression-free survival rates were also evaluated. Results: Following induction therapy, the overall response rate was obtained in 71% of patients, including a CR/sCR of 10% and a very good partial response (VGPR) of 26%. Twenty-six of the 42 patients completed ASCT following the protocol and CR/sCR and VGPR rate 100 days after ASCT was 26% and 17%, respectively. During consolidation therapy, 3 of the 24 patients achieved deeper responses. Eight of the 18 patients completed 2-year bortezomib maintenance without disease progression and grade 3/4 toxicities. Five patients were VGPR or partial response after ASCT but maintained response with 2-year bortezomib maintenance. Two-year overall and progression-free survival rates were 92.5% (95% confidence interval [CI]: 78.5%−97.5%) and 62.6% (95% CI: 45.8%−75.5%), respectively. Grade 3/4 toxicities (≥ 10%) included neutropenia (19%) and anemia (17%) in induction, and thrombocytopenia (29%) in consolidation. Conclusion: VCD induction/consolidation and bortezomib maintenance with ASCT for NDMM resulted in a high CR/sCR rate and provided good overall/progression-free survival in Japan.